KEPEMILIKAN MANAJERIAL, KEPEMILIKAN INSTITUSIONAL DAN KOMITE AUDIT TERHADAP NILAI PERUSAHAAN PADA PERUSAHAAN PADA PERUSAHAAN MANUFAKTUR SUBSEKTOR MAKANAN DAN MINUMAN YANG TERDAFTAR DI BURSA EFEK INDONESIA TAHUN 2018-2021 - Orlando Christhoper Torondek; Remista Simbolon (Universitas Sains dan Teknologi Komputer, 2022)
Abstract. The purpose of this study is to determine the effect of managerial ownership, institutional ownership and audit committee variables on the value of the company. The method used is descriptive method. The population in this study is a food and beverage sub-sector manufacturing company listed on the Indonesia Stock Exchange in 2018-2021. The Total data used from 11 companies is 44 data. The final results showed that managerial ownership, institutional ownership and audit committee significantly affect the value of the company.. Keywords: Managerial Ownership, Institutional Ownership, Audit Committee, Company Value